Pick's currency yearbook, 1974 : Now World currency yearbook - International Currency Analysis, Inc. (New York : Pick Publishing Corporation, 1974)
Annual compendium on currencies worldwide. Includes information on the economic status of countries and black market exchange rates. The title changed in 1980 but all volumes are located under the same call number.
lje 19/10/18
Reference
Keywords: Money; Valuta's.; Geld; Geldpolitik; Wechselkurs; Welt; Money; Monnaie